De Facto Control of Territory in International Law: A Study into the Rights and Obligations of States in Disputed Territories - Crosato Neumann, Alfredo Carlos Ricardo (2016)
Abierto en el repositorio institucional de la Graduate Institute Geneva: https://repository.graduateinstitute.ch/record/294399